Pertanggung Jawaban Pelaku Tindak Pidana Penggelapan Dalam Perspektif Hukum KUHP 374 - Ine Pebrianti Harahap; Hamidatul Luhuriyah; Fauziah Lubis (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
The crime of offense in the office is governed by article 374 of the code of criminal code, is a criminal offence from the evasion in the basic form of article 372 of the criminal code.This crime is closely related to morals and belief in someone's honesty which leads to a lie about that belief that takes advantage of the position itself. This research aims to determine the legal regulation of the crime of embezzlement in office, and to know the law enforcement against the perpetrators of the crime of embezzlement in office in Decision Number 112/PID.B/2021/PN. This research uses normative research type. Embezzlement In Office, Embezzlement, Crime